(untitled) - Rodrigo Duarte (O Que Nos Faz Pensar, 2016)
Some discussions in contemporary aesthetics, as, for instance, the one by Arthur  Danto, focusing the thematic of realism in the visual arts brought to light the  question of a possible relevance of this topic not only for other artistic métiers but  also for the philosophy of art in general. Taking this debate into account, it seems  interesting to highlight the theme of realism in Theodor Adorno’s Aesthetic theory,  which in its more than five hundred pages in the German original, approaches the  notion of realism under several viewpoints. This article focuses on realism under  the following viewpoints: the loss of import of art, the relationship between art and  society, the relationship between expression and construction and the character of  appearance and enigma of artworks.